Analysis of the synergistic antifungal mechanism of eugenol and citral. (April 2020) - Ju, Jian; Xie, Yunfei; Yu, Hang; Guo, Yahui; Cheng, Yuliang; Qian, He; Yao, Weirong
Abstract: The synergistic effects of different essential oils can not only reduce their dosage and cost, but also improve their biological activity. The aim of this study was to evaluate the synergistic antifungal effect of eugenol and citral (SEC ) on Penicillium roqueforti . Determination of reactive oxygen species (ROS) and malondialdehyde content indicated that SEC could induce membrane lipid peroxidation, and the contribution of citral was greater than that of eugenol. In addition, downregulation of the gene encoding an NADPH oxidase subunit indicated that the ROS burst induced by SEC was mediated by NADPH oxidase. Scanning electron microscope (SEM) and transmission electron microscope (TEM), propidium iodide treatment, DNA gel electrophoresis and cell leakage experiments showed that SEC destroyed the integrity of the cell membrane and internal structures, and degraded the cell contents, and the contribution of eugenol was greater than that of citral. These results showed that SEC inhibited the activity of P. roqueforti more effectively than eugenol or citral alone, by inducing membrane lipid peroxidation and promoting the ability of eugenol to destroy the cell membrane. The combined agents eventually caused leakage of the cell contents, and ultimately cell death. Highlights: The combination of eugenol and citral (SEC ) had synergistic inhibition effect against P. roqueforti. SEC treatment could significantly induce lipid peroxidation. SEC treatment resulted in damaged the morphology of cells. SEC treatment resulted in loss of plasma membrane integrity.